Lon fuller, Pembuatan Undang-undang dan Penafsiran Hukum - Widjaja, Gunawan (Pelita Harapan University, 2006)
Laws are made to create legal certainty for the society. Globalization has caused the mingling of legal system and legal tradition. Fuller offered 8 desiderata, the requirements need to make good laws. By following the 8 desiderata, the laws made by legislative body shall provide legal order in the society. The 8 desiderata are generality, promulgation, prospectivity, clarity, consistency or avoiding contradiction, possibility of obedience, constancy through time or avoidance of frequent change, congruence between official action and declared rules. To achieve congruence between official action and declared rules, interpretation plays very important rules. Each legal tradition has its own way of interpretation. One should not use the wrong conception of interpretation otherwise it will create chaos in the society.